2022
DOI: 10.3390/oxygen2020015
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Its Role in Cd-Induced Epigenetic Modifications: Use of Antioxidants as a Possible Preventive Strategy

Abstract: Oxidative stress (OS) represents one of the main mechanisms of toxicity induced by environmental pollutants such as cadmium (Cd). OS is a natural physiological process where the presence of oxidants, such as reactive oxygen-derived species (ROS), outweighs the strategy of antioxidant defenses, culminating in the interruption of signaling and redox control. It has been suggested that Cd increases ROS mainly by inducing damage to the electron transport chain and by increasing the activity of nicotinamide adenine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 278 publications
0
7
0
2
Order By: Relevance
“…[101,102] When Cd exposure occurs, there is an increased TET expression with less expression of DNMT activity causing hypomethylation, whereas Cd also increases DNMT1 and DNMT3A expression thereby leading to hypermethylation. [103] This discrepancy of Cd on DNA methylation depends on duration and level of exposure. In AD, the methylation induces promoter CDK5 hypomethylation of APP, PSEN1, PSEN2, and GSK3β genes and also, hypermethylation of ANK1, RPL13, RHBDF2, DUSP22, and SORL1 genes.…”
Section: Toxic Induced Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…[101,102] When Cd exposure occurs, there is an increased TET expression with less expression of DNMT activity causing hypomethylation, whereas Cd also increases DNMT1 and DNMT3A expression thereby leading to hypermethylation. [103] This discrepancy of Cd on DNA methylation depends on duration and level of exposure. In AD, the methylation induces promoter CDK5 hypomethylation of APP, PSEN1, PSEN2, and GSK3β genes and also, hypermethylation of ANK1, RPL13, RHBDF2, DUSP22, and SORL1 genes.…”
Section: Toxic Induced Dna Methylationmentioning
confidence: 99%
“…However, minimal research has been focused on Cd exposure affecting histone methylation, acetylation, and phosphorylation by changing the enzyme expression that alters them. [ 103 ] In vitro investigations have primarily been used to describe Cd‐induced histone changes. At the metallothionein 3 (MT3) promoter region, Cd‐exposed cells had higher levels of H3K4me3, H3K27me3, and H3K9me3.…”
Section: Introductionmentioning
confidence: 99%
“…For example, research on liver cells revealed that Cd treatment significantly decreased the activities of SOD and CAT and increased the levels of lipid peroxidation products, demonstrating how Cd aggravates oxidative stress by impairing the antioxidant enzyme system [ 40 ]. Additionally, Cd inhibits the synthesis and promotes the depletion of glutathione (GSH), a crucial intracellular antioxidant molecule, further reducing intracellular GSH levels and weakening the antioxidant capacity of cells [ 41 ].…”
Section: Oxidative Stress Caused By Cadmiummentioning
confidence: 99%
“…Hong and Gurjit (2012) assert that exposure to particulate matter can induce glutathione depletion in the methylation cycle, thereby promoting epigenetic changes, whereas Madrigano et al (2012) established that PAHs form adducts inducing DNA methylation (hypo and hyper) of specific genes linked to physiological dysfunctions and contribute more to the occurrence and development of diseases ( Cao et al, 2020 ). Hernández-Cruz et al (2022) also reviewed cadium-induced epigenetic alterations and the use of antioxidant compounds to counteract Cd-induced epigenetic alterations.…”
Section: Gene-antioxidant Modulation and Hydrocarbon Tolerancementioning
confidence: 99%